Impact of Natural Enemies on Pest Population in Cotton Monocrop and Cotton Intercropped with Soybean - Mahendra, K. R.; Chaitanya, M.; Anitha, G.; Manjunatha, B.; Lakshmi, K. S. Ishwarya (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
An experiment was conducted to study the impact of natural enemies on pests of cotton, when it was grown as monocrop and as intercrop with soybean. A comparison of diversity and abundance of pests and natural enemies of cotton monocrop in Rajendranagar (unprotected) and Adilabad (protected) was also made. Observations on pests and natural enemies were taken by using various sampling methods and correlation between pest and natural enemy population were estimated. Results revealed that in intercropped cotton, Coccinellidae, Spiders, Staphylinidae and Anthocoridae were the major predator taxa which have impacted the population levels of sucking pest’s taxa such as Cicadellidae, Aleyrodidae Aphididae, Miridae and Thripidae. However, in mono-cropped cotton, Spiders found to have little or no impact on pest population, suggesting plant diversification is playing crucial in predators’ activity. Further, the diversity of predators in un-sprayed Rajendranagar fields were comparatively higher (1.66) than the sprayed Adilabad cotton fields (1.62). Similarly, the evenness of predators in un-sprayed Rajendranagar fields were comparatively higher (1.37) than the sprayed Adilabad cotton fields (1.12). These results suggest that, intra crop diversification without or minimal use of insecticides allows the natural enemies to perform their part of job as natural regulates of pest populations which minimizes the cost of cultivation with added benefit from the intercrop.